Trade-offs inside the black box of neoantigen prediction - Yao, Ning; Greenbaum, Benjamin D (Immunity (Cambridge, Mass.), 2023)
Success of precision neoantigen-based immunotherapies hinges on the selection of immunogenic neoantigens, yet currently neither large-scale datasets nor streamlined methods are available to achieve this goal. Müller et al. present a large experimental dataset resource along with machine learning-based models to classify immunogenic neoantigens.